DAPL1 is activated by Np63 and GRα and regulates lipid metabolism - Heung-Seok Bae; Yong-In Kim; DongWook Kim; Ki-Hoan Nam; KyungSook Han; SunJo Kim; SungWon Kwon; Je-Yoel Cho (Journal of Molecular Medicine, 2026)
Non-small cell lung cancer (NSCLC) accounts for about 80% of all lung cancer occurrences and is divided into largely Adenocarcinoma (LUAD), Squamous cell carcinoma (LUSC), and Large cell carcinoma. In this study, using RNA-seq data between cancer tissues and adjacent normal tissues of 5 LUAD and 4 LUSC patients, we found that a Death associated protein like 1 (DAPL1) was highly expressed in squamous cell carcinoma but not in adenocarcinoma. Through the RNA-seq analysis, we found that lipid metabolic pathway genes Fdft1, Pcyt1a, and Sptlc1 correlate well with DAPL1 level changes in LUSC. We also found that Dapl1 was activated by Np63 and GRα monomer transcription factors. We generated a DAPL1 knockout mouse, which shows body weight and hair color changes, implying the role of DAPL1 in lipid metabolism. Our data show that Np63, GRα transcription factors activate DAPL1, and it is predicted to contribute to cellular acidification by regulating lipid metabolism based on mRNA-seq data and DAPL1 KO mice. Key messages This study uses RNA-seq data between cancer tissues and adjacent normal tissues of 5LUAD and 4LUSC patients. We found that a Death associated protein like 1 (DAPL1) was highly expressed in squamous cell carcinoma but not in adenocarcinoma. We also found that Dapl1 was activated by Np63 and GRα monomer transcription factors. The RNA-seq analysis found that lipid metabolic pathway genes Fdft1, Pcyt1a, and Sptlc1 correlate well with DAPL1 level changes in LUSC. We generated a DAPL1 knockout mice. DAPL1 KO mice were bred at two institutions (KRIBB for phonotypes, and SNU for functions). Interestingly, in KRIBB, DAPL1 KO body weight was lower than WT, and in SNU, DAPL1 KO body weight was higher than WT. In the investigation of mouse chow from the two institutions, differences in choline were noted. When chow with differences only in choline was produced and applied to new DAPL1 KO mice, the same results were obtained. Through RNA-seq data and body weight changes in DAPL1 KO mice, we report that DAPL1 regulates cholesterol, PC, and SM through changes in mRNA of Fdft1, Pcyt1a, and Sptlc1. Our data show that Np63, GRα monomer transcription factors activate DAPL1, and it is predicted to regulate lipid metabolism based on mRNA-seq data and DAPL1 KO mice.

A new integrated process from non-edible biomass to 2,5-furandicarboxylic acid via 5-bromomethylfurfural and 5-acetoxymethylfurfural intermediates - In Yong Eom; Jihoon Kim; Jiyun Yoo; Gihyun Kwon; Maeum Lee; Faraz Muhammad Abbasi; Bolla Srinivasa Rao; Heedo Ryou; Jeehoon Han; Dong Won Hwang (Chemical Engineering Journal, 2026)

Genome-scale model-guided microbial engineering for valorization of agricultural waste biomass to poly(3-hydroxybutyrate) - Chae-Rim Jeong; Jaeseong Hwang; Young-Kwon Park; Jae Yong Ryu; Yong Hee Han; Ji Young Jeong; In Min Hwang; Ryeongeun Kim; Jung Eun Yang (Bioresource Technology, 2026)

Comparative responses of fruit quality attributes, mineral nutrients, and targeted metabolites in fruit of early- to mid-season apple cultivars at harvest - Jinhee Lee; Hnin Phyu Lwin; Seung Yeon Han; Si-Eun Byeon; Hyowon Park; Theint Thandar Latt; Jiwon Park; Sooyeon Lim; Jong Taek Park; Ha-il Jung; Dagyeong Kwon; Jeong Hee Kim; et al. (Horticulture, Environment, and Biotechnology, 2026)

Near-infrared light–responsive implantable module integrated into glaucoma drainage device for controlled antifibrotic drug therapy - Chang Hee Min; Young In Shin; Han Bi Ji; Soo Bin Yoon; Yeonseo Kim; Cho Rim Kim; Jae Hoon Han; Min Ji Kim; Myung Ju Kim; Eun Jung Kwon; Young Kook Kim; Ki Ho Park; et al. (Chemical Engineering Journal, 2026)

Fine-grained surface sediment provenance in the Hupo Basin, Eastern Coast of Korea - In Kwon Um; Man Sik Choi; Jang-Jun Bahk; Soo Yeon Han (Geo-Marine Letters, 2026)

Estimation of BPA, BPS, and BPF exposure levels in the general Korean population using the physiologically-based toxicokinetic model and human urinary biomonitoring for risk assessment - Min-Ju Kim; Yong-Kook Kwon; Hyung-Jun Kim; Dong-Gyun Han; In-Soo Yoon; Seungyoung Park; Gunyoung Lee; Hye Young Lee (International Journal of Hygiene and Environmental Health, 2025)

Large seasonal variations in distributions, sources, and fluxes of dissolved amino acids in the continental shelf water - Hyekyung Park; Guebuem Kim; Nahyeon Kwon; Hanbyul Lee; Heejun Han; Joon-Soo Lee; In-Seong Han (Progress in Oceanography, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Revisiting elemental geochemistry in surface sediments of the Ulleung Basin, East/Japan Sea: Signals from ocean dumping materials - In Kwon Um; Man Sik Choi; Soo Yeon Han; Seonghu Choi; Dasom Yang (Marine Pollution Bulletin, 2024)

Effects of the physical structure and surface charge of activated carbon on the reduction of biogenic amines in anchovy fish sauce - Kil Bo Shim; Jung-Jin In; Jong Bong Lee; Hyeong Gu Han; Seong Ah Son; Woo Jin Lee; Yeon Joo Bae; Ga Yeon Kwon; Byoung Kyu An (Food Chemistry, 2024)

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

Cell death induction and intracellular vesicle formation in human colorectal cancer cells treated with Δ9-Tetrahydrocannabinol - Yu-Na Hwang; In-Seo Kwon; Ju-Hee Park; Han-Heom Na; Tae-Hyung Kwon; Jin-Sung Park; Keun-Cheol Kim (Genes & Genomics, 2023)
Background Δ 9 -Tetrahydrocannabinol (Δ 9 -THC) is a principal psychoactive extract of Cannabis sativa and has been traditionally used as palliative medicine for neuropathic pain. Cannabidiol (CBD), an extract of hemp species, has recently attracted increased attention as a cancer treatment, but Δ 9 -THC is also requiring explored pharmacological application. Objective This study evaluated the pharmacological effects of Δ 9 -THC in two human colorectal cancer cell lines. We investigated whether Δ 9 -THC treatment induces cell death in human colorectal cancer cells. Methods We performed an MTT assay to determine the pharmacological concentration of Δ 9 -THC. Annxein V and Western blot analysis confirmed that Δ 9 -THC induced apoptosis in colorectal cancer cells. Metabolic activity was evaluated using MitoTracker staining and ATP determination. We investigated vesicle formation by Δ 9 -THC treatment using GW9662, known as a PPARγ inhibitor. Results The MTT assay showed that treatment with 40 μM Δ 9 -THC and above inhibited the proliferation of colorectal cancer cells. Multiple intracytoplasmic vesicles were detected upon microscopic observation, and fluorescence-activated cell sorting analysis showed cell death via G1 arrest. Δ 9 -THC treatment increased the expression of cell death marker proteins, including p53, cleaved PARP-1, RIP1, and RIP3, suggesting that Δ 9 -THC induced the death of colorectal cancer cells. Δ 9 -THC treatment also reduced ATP production via changes in Bax and Bcl-2. Δ 9 -THC regulated intracytoplasmic vesicle formation by modulating the expression of PPARγ and clathrin, adding that antiproliferative activity of Δ 9 -THC was also affected. Conclusion In conclusion, Δ 9 -THC regulated two functional mechanisms, intracellular vesicle formation and cell death. These findings can help to determine how cannabinoids can be used most effectively to improve the efficacy of cancer treatment.

Long-term changes in the concentrations of nutrients in the marginal seas (Yellow Sea, East China Sea, and East/Japan Sea) neighboring the Korean Peninsula - Sojin Park; Guebuem Kim; Hyeong Kyu Kwon; In-Seong Han (Marine Pollution Bulletin, 2023)

Rational design of composite supporting electrolyte required for achieving high performance aqueous organic redox flow battery - Wonmi Lee; Kyu In Shim; Gyunho Park; Jeong Woo Han; Yongchai Kwon (Chemical Engineering Journal, 2023)

Data-driven modeling of multimode chemical process: Validation with a real-world distillation column - Yeongryeol Choi; Bhavana Bhadriaju; Hyungtae Cho; Jongkoo Lim; In-Su Han; Il Moon; Joseph Sang-Il Kwon; Junghwan Kim (Chemical Engineering Journal, 2023)

Improvement of IgA Nephropathy and Kidney Regeneration by Functionalized Hyaluronic Acid and Gelatin Hydrogel - Sureerat Khunmanee; So Young Chun; Yun-Sok Ha; Jun Nyung Lee; Bum Soo Kim; Wei-Wei Gao; In Yong Kim; Dong Keun Han; Seungkwon You; Tae Gyun Kwon; Hansoo Park (Tissue Engineering and Regenerative Medicine, 2022)

Latest Quaternary mass-transport processes of fan-shaped body in the western margin of the Ulleung Basin, East Sea (Japan Sea) - Sang-Hoon Lee; Hyeong-Tae Jou; Jang-Jun Bahk; Hyunggu Jun; Seong-Hoon Moon; Han-Joon Kim; Senay Horozal; Deniz Cukur; In-Kwon Um; Dong-Geun Yoo; Roger Urgeles (Geosciences Journal, 2021)

Resolvin D3 Promotes Inflammatory Resolution, Neuroprotection, and Functional Recovery After Spinal Cord Injury - Juri Kim; Hari Prasad Joshi; Seung Hun Sheen; Kyoung-Tae Kim; Jae Won Kyung; Hyemin Choi; Ye Won Kim; Su Yeon Kwon; Eun Ji Roh; Un Yong Choi; Seil Sohn; Yong Ho Kim; et al. (Molecular Neurobiology, 2021)

Vildagliptin, an Anti-diabetic Drug of the DPP-4 Inhibitor, Induces Vasodilation via Kv Channel and SERCA Pump Activation in Aortic Smooth Muscle - Mi Seon Seo; Hongliang Li; Jin Ryeol An; In Duk Jung; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Il-Whan Choi; Won Sun Park (Cardiovascular Toxicology, 2019)

Ursodeoxycholic Acid Inhibits Inflammatory Responses and Promotes Functional Recovery After Spinal Cord Injury in Rats - Wan-Kyu Ko; Seong Jun Kim; Min-Jae Jo; Hyemin Choi; Donghyun Lee; Il Keun Kwon; Soo-Hong Lee; In-Bo Han; Seil Sohn (Molecular Neurobiology, 2019)

Association of glutathione S-transferase M1 and T1 null/present polymorphism with physical performance in the Korean population - In Wook Hwang; Kicheol Kim; Bit Na Kwon; Hyung Jun Kim; Seung Hun Han; Noo Ri Lee; Eun Ji Choi; Hyun Ik Cho; Han Jun Jin (Genes & Genomics, 2019)

Genetic associations between ADHD and dopaminergic genes (DAT1 and DRD4) VNTRs in Korean children - Jun Ho Hong; In Wook Hwang; Myung Ho Lim; Ho Jang Kwon; Han Jun Jin (Genes & Genomics, 2018)

Development of an Observation Processing Package for Data Assimilation in KIAPS - Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Ji-Hyun Ha; Hyo-Jong Song; In-Hyuk Kwon; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Effects of 7-MEGA TM 500 on Oxidative Stress, Inflammation, and Skin Regeneration in H 2 O 2 -Treated Skin Cells - In-Bong Song; Hyejung Gu; Hye-Ju Han; Na-Young Lee; Ji-Yun Cha; Yeon-Kyong Son; Jungkee Kwon (Toxicological Research, 2018)

Effects of 1-methylcyclopropene (1-MCP) and polyethylene (PE) film liner treatments on the fruit quality of cold-stored ‘Gamhong’ apples - Kyoung-ook Kim; Jingi Yoo; Jinwook Lee; Nay Myo Win; Seulgi Ryu; Jeung-Sul Han; Hee-Young Jung; Myoung-Gun Choung; Yong-Deuk Kwon; Dong Hoon Lee; In-Kyu Kang (Horticulture, Environment, and Biotechnology, 2018)

Development of predicting method for dynamic pile behavior by using centrifuge tests considering the kinematic load effect - Min-Taek Yoo; Jin-Tae Han; Jung-In Choi; Sun-Yong Kwon (Bulletin of Earthquake Engineering, 2017)

Effective selection of soybean cultivars to wildfire disease pathogen Pseudomonas amygdali pv. tabaci - In Jeong Kang; Seung-Han Kim; Yong Weon Seo; Min Jeong Seo; Hyeong Kwon Shim; Dong Bum Shin; Sunggi Heu (Journal of Crop Science and Biotechnology, 2015)

Ectopic expression of a hot pepper bZIP-like transcription factor in potato enhances drought tolerance without decreasing tuber yield - Seok-Jun Moon; Se-Youn Han; Dool-Yi Kim; In Sun Yoon; Dongjin Shin; Myung-Ok Byun; Hawk-Bin Kwon; Beom-Gi Kim (Plant Molecular Biology, 2015)

Erratum to: Effects of different selenium levels on growth and regulation of laccase and versatile peroxidase in white-rot fungus, Pleurotus eryngii - Yong Hyun Kim; Hyoun-Su Lee; Hyun-Jung Kwon; Bharat Bhusan Patnaik; Kung-Woo Nam; Yeon Soo Han; In-Seok Bang; Man-Deuk Han (World Journal of Microbiology and Biotechnology, 2014)

Human hair keratin and its-based biomaterials for biomedical applications - Hanna Lee; Kwantae Noh; Sang Cheon Lee; Il-Keun Kwon; Dong-Wook Han; In-Seop Lee; Yu-Shik Hwang (Tissue Engineering and Regenerative Medicine, 2014)

Effects of different selenium levels on growth and regulation of laccase and versatile peroxidase in white-rot fungus, Pleurotus eryngii - Yong Hyun Kim; Hyoun-Su Lee; Hyun-Jung Kwon; Bharat Bhusan Patnaik; Kung-Woo Nam; Yeon Soo Han; In-Seok Bang; Man-Deuk Han (World Journal of Microbiology and Biotechnology, 2014)

Ectopic expression of CaWRKY1, a pepper transcription factor, enhances drought tolerance in transgenic potato plants - Seok-Jun Moon; Se-Youn Han; Dool-Yi Kim; Beom-Gi Kim; In Sun Yoon; Dongjin Shin; Hawk-Bin Kwon; Myung-Ok Byun (Journal of Plant Biology, 2014)

Ionizing radiation-inducible microRNA miR-193a-3p induces apoptosis by directly targeting Mcl-1 - Jeong-Eun Kwon; Bu-Yeon Kim; Seo-Young Kwak; In-Hwa Bae; Young-Hoon Han (Apoptosis, 2013)

OsREL2, a rice TOPLESS homolog functions in axillary meristem development in rice inflorescence - Yerim Kwon; Si-in Yu; Joo-hyuk Park; Ying Li; Jin-Hee Han; Hemasundar Alavilli; Jung-Il Cho; Tae-Houn Kim; Jong-Seong Jeon; Byeong-ha Lee (Plant Biotechnology Reports, 2012)

Potential increase of flood hazards in Korea due to global warming from a high-resolution regional climate simulation - Eun-Soon Im; Byong-Ju Lee; Ji-Hye Kwon; So-Ra In; Sang-Ok Han (Asia-Pacific Journal of Atmospheric Sciences, 2012)

Isolation of an Rx homolog from C. annuum and the evolution of Rx genes in the Solanaceae family - Jinxia Shi; Seon-In Yeom; Won-Hee Kang; Min-Kyu Park; Doil Choi; Jin-Kyung Kwon; Jung-Heon Han; Heung-Ryul Lee; Byung-Dong Kim; Byoung-Cheorl Kang (Plant Biotechnology Reports, 2011)

Tropical cyclone track and intensity prediction with a structure adjustable balanced vortex - Hyeong-Bin Cheong; In-Hyuk Kwon; Hyun-Gyu Kang; Ja-Rin Park; Hyun-Jun Han; Jae-Jin Kim (Asia-Pacific Journal of Atmospheric Sciences, 2011)

Structure change of Typhoon Nari (2007) in the weakening stage - In-Hyuk Kwon; Hyeong-Bin Cheong; Hyun-Gyu Kang; Hyun-Jun Han; Ja-Rin Park (Asia-Pacific Journal of Atmospheric Sciences, 2010)

15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) sensitizes human leukemic HL-60 cells to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis through Akt downregulation - Hoon Han; Sung-Won Shin; Chi-Yeon Seo; Hyuk-Chan Kwon; Jin-Yeong Han; In-Hoo Kim; Jong-Young Kwak; Joo-In Park (Apoptosis, 2007)

Enhanced brain targeting efficiency of intranasally administered plasmid DNA: an alternative route for brain gene therapy - In-Kwon Han; Mi Young Kim; Hyang-Min Byun; Tae Sun Hwang; Jung Mogg Kim; Kwang Woo Hwang; Tae Gwan Park; Woon-Won Jung; Taehoon Chun; Gil-Jae Jeong; Yu-Kyoung Oh (Journal of Molecular Medicine, 2006)

Biflavonoids inhibited phosphatase of regenerating liver-3 (PRL-3) - Sung-Kyu Choi; Hyun-Mi Oh; Su-Kyung Lee; Dae Gwin Jeong; Seong Eon Ryu; Kwang-Hee Son; Dong Cho Han; Nack-Do Sung; Nam-In Baek; Byoung-Mog Kwon (Natural Product Research, 2006)

Cyclic diarylheptanoids inhibit cell-mediated low-density lipoprotein oxidation - Hyun-Mi Kang; Ju Ryong Kim; Tae-Sook Jeong; Sung-Gyu Choi; Young-Han Ryu; Goo Taeg Oh; Nam-In Baek; Byoung-Mog Kwon (Natural Product Research, 2006)

Cyclic diarylheptanoids inhibit cell mediated low-density lipoprotein oxidation - Hyun-Mi Kang; Ju Ryong Kim; Tae-Sook Jeomg; Sung-Gyu Choi; Young-Han Ryu; Goo Taeg Oh; Nam-In Baek; Byoung-Mog Kwon (Natural Product Research, 2006)

Novel Leuconostoc citreum starter culture system for the fermentation of kimchi, a fermented cabbage product - In-Kwon Choi; Seok-Ho Jung; Bong-Joon Kim; Sae-Young Park; Jeongho Kim; Hong-Ui Han (Antonie van Leeuwenhoek, 2003)

Influence of reducing agents on the secretion rate of recombinant erythropoietin from CHO cells - Sung Kwan Yoon; Yong-Ho Ahn; In-Chan Kwon; Kyuboem Han; Ji Yong Song (Biotechnology Letters, 1998)